PENGARUH PENGENDALIAN INTERNAL, BUDAYA ETIS ORGANISASI DAN KETAATAN ATURAN AKUNTANSI TERHADAP KECENDERUNGAN KECURANGAN AKUNTANSI PADA DINAS PPKUKM DKI JAKARTA - Pratama Ziefa, Alvinsyah; ., Ratiyah; hartanti; Setyaningsih, Eka Dyah (Account: Jurnal Akuntansi, Keuangan dan Perbankan, 2023)
Accounting fraud is an act of manipulating or falsifying financial statement data, engaging in acts of corruption, or using assets improperly to generate profits. Central and local governments currently experience corruption cases every year. This is due to the factors that influence the occurrence of fraud. This study aims to determine the effect of internal control, organizational ethical culture and compliance with accounting rules on the tendency of accounting fraud at the DKI Jakarta PPKUKM Office. The population in this study were 95 employees of the DKI Jakarta PPKUKM Office. The sampling technique is using total sampling. The data collection method in this study is a survey method using a questionnaire. The data analysis technique is using multiple linear regression analysis. The results of this study indicate that internal control has a significant effect on the tendency of accounting fraud, this is evidenced by the t value (2.176) > t table (1.670) and a significance value of 0.033 <0.05. Organizational ethical culture has a significant negative effect on the tendency of accounting fraud, this is evidenced by the t value (-2.335) > t table (1.670) and a significance value of 0.023 <0.05. Obedience to accounting rules has a significant negative effect on the tendency of accounting fraud, this is evidenced by the t value (-2.204) > t table (1.670) and a significance value of 0.031 <0.05. Internal control, organizational ethical culture, and adherence to accounting rules simultaneously affect the tendency of accounting fraud, this is evidenced by the calculated F value (8.658)> F table (2.751), and a significance value of 0.000 <0.05.